2022
DOI: 10.3390/ijerph19031453
|View full text |Cite
|
Sign up to set email alerts
|

Usability and Engagement Testing of mHealth Apps in Paediatric Obesity: A Narrative Review of Current Literature

Abstract: Mobile health (mHealth) platforms have become increasingly popular for delivering health interventions in recent years and particularly in light of the COVID-19 pandemic. Childhood obesity treatment is an area where mHealth interventions may be useful due to the multidisciplinary nature of interventions and the need for long-term care. Many mHealth apps targeting youth exist but the evidence base underpinning the methods for assessing technical usability, user engagement and user satisfaction of such apps with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…A recent review noted that usability is not fixed, and that evaluations of ‘technical usability’ (ie, quantitative assessments, scale-based questionnaires) and qualitative usability insights are only relevant in the context where they are applied. 25 26 Technical usability has been further defined as the capability for a technology to be understood, learnt, used and attractive to the user when used under specified conditions. 27 It has been (boldly) suggested that up to 80% of usability problems can be identified by using as few as five subjects and further, that almost all of high-severity usability problems can be uncovered with usability assessment by only three subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review noted that usability is not fixed, and that evaluations of ‘technical usability’ (ie, quantitative assessments, scale-based questionnaires) and qualitative usability insights are only relevant in the context where they are applied. 25 26 Technical usability has been further defined as the capability for a technology to be understood, learnt, used and attractive to the user when used under specified conditions. 27 It has been (boldly) suggested that up to 80% of usability problems can be identified by using as few as five subjects and further, that almost all of high-severity usability problems can be uncovered with usability assessment by only three subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review noted that usability is not fixed, and that evaluations of ‘technical usability’ (ie, quantitative assessments, scale-based questionnaires) and qualitative usability insights are only relevant in the context where they are applied 25 26. Technical usability has been further defined as the capability for a technology to be understood, learnt, used and attractive to the user when used under specified conditions 27.…”
Section: Discussionmentioning
confidence: 99%
“…Software requirements should meet users' stated requirements in this perspective too, otherwise it may loose users' acceptance. A website exhibiting bad usability is losing its acceptance from potential users [12,13]. Software and technology developers focus heavily on usability testing to assessthe realistic usefulness of their products before the product actually reach commercial users.…”
Section: Related Workmentioning
confidence: 99%
“…In another study, usability testing evaluated mhealth apps in paediatric obesity. The findings of the study identified the importance of thorough evaluation and collection of evidence in mhealth apps for best practice [47].…”
Section: Are Interactions Consistent and Intuitive Across All Screens?mentioning
confidence: 99%